SENIOR HIGH SCHOOL STUDENTS’ LEARNING EXPERIENCES OF ONLINE ENGLISH LEARNING DURING PANDEMIC - Puput Khoirunnisaa (Berajah Journal, 2022)
Senior high school students have to take English subjects since it is essential in senior high school in Indonesia. However, due to CoVID-19 outbreaks, all activities are stopped, including the Educational Institution, which is forced every school to shift from face-to-face learning to online English learning. This situation leads students to experiences a lot of new things during the learning process. It does not only lead to generating various experiences but also various problems as well. This study was conducted at Senior High School in Sidoarjo, Indonesia. The main aim of the study was to explore the most useful online learning platform for learning English and to investigate the students’ learning experiences in terms of the technological devices used for online English learning, the quality of online English learning, and the issues regarding online English learning during COVID-19 pandemic. This study used the quantitative research method to get numerical data. In this research, online-administered questionnaires were used to gather data. The finding indicated that the most useful online learning platform is Google Classroom. However, the students also experienced some issues regarding learning material, time management, enthusiasm, study environment, assignments, and internet access and technology accessibility.